High‐throughput membrane‐anchored proteome screening reveals PIEZO1 as a promising antibody‐drug target for human esophageal squamous cell carcinoma. (24th May 2022) - Qin, Xun; Ni, Zhen; Jiang, Jianjun; Liu, Xiguang; Dong, Xiaoying; Li, Mei; Miao, Kai; Rao, Shuan; Zhang, Wenqing; Cai, Kaican
Abstract: Background: Esophageal carcinoma is one of the most fatal cancers worldwide. In China, over 90% of esophageal cancer patients are diagnosed with esophageal squamous cell carcinoma (ESCC). Currently, the survival and prognosis of ESCC patients are not satisfying because of insufficient early screening and lack of efficacious medication. Accumulating studies have suggested that antibody‐drug conjugates (ADC) represent a promising antitumor strategy. Method: Here, we carried out a specific membrane proteome screening with ESCC patients' samples using a high‐throughput antibody microarray to uncover potential targets for ADC development. Candidates were validated with expression and cytotoxicity evaluation both in vitro and in vivo. Results: Our data have shown that the Piezo‐Type Mechanosensitive Ion Channel Component 1 (PIEZO1) is particularly overexpressed in human ESCC tumors and can be efficiently internalized when bound with its monoclonal antibody. Furthermore, the PIEZO1 antibody combined with monomethyl auristatin E (MMAE) can specifically kill PIEZO1 high‐expressed ESCC tumor cells by inducing cell cycle arrest and apoptosis. More importantly, the Anti‐PIEZO1‐MMAE can significantly suppress tumor progression in ESCC xenograft tumor models without any obvious side effects. Conclusion: Taken together, our work demonstrates that PIEZO1 is a promising target to develop ADCs for human ESCC treatment, providing a new strategy for ESCC patients' personalized therapy. Abstract : Piezo‐Type Mechanosensitive Ion Channel Component 1 (PIEZO1) is significantly over‐expressed in a large proportion (50%) of ESCC patients. Tumor cell surface located PIEZO1 could be internalized with the binding of its monoclonal antibody. Anti‐PIEZO1‐MMAE can induce cell cycle arrest and apoptosis of ESCC cells in vitro and suppress ESCC tumor cell growth in vivo without any obvious side effect